Fracture during oral bisphosphonate therapy is associated with deteriorated bone material strength index - Nogués, X; Prieto-Alhambra, D; Güerri-Fernández, R; Garcia-Giralt, N; Rodriguez-Morera, J; Cos, L; Mellibovsky, L; Pérez, A (Elsevier, 2017)
BACKGROUND: Some patients experience fractures while receiving oral bisphosphonates (BPs) treatment. Clinical risk factors, advanced bone density loss, and microarchitecture deterioration have been associated with such fractures but bone tissue properties other than bone mineral density (BMD) have not been assessed. METHODS: In a cross-sectional study of postmenopausal women on bisphosphonates for at least 4years with good adherence to treatment, 21 patients with incident fractures were compared with 18 treated patients without new fractures. Demographic and clinical variables, BMD, laboratory tests, and bone material strength index (BMSi) assessed by impact microindentation at the tibial diaphysis were recorded for all participants. RESULTS: Clinical and laboratory results did not differ between patients taking BPs with incident fractures and those without new fractures. However, BMSi was significantly lower (mean±SD) in those who fractured (73.76±6.49) than in no-fracture patients (81.64±6.26; p=0.001). Lumbar spine (LS) BMD was also lower in fractured patients (p=0.03). Adjusted models including age, body mass index, years on BP treatment, and LS-BMD confirmed an increase in fracture risk per BMSi standard deviation decrease: adjusted OR 23.5 [95% CI 2.16 to 255.66], p=0.01. ROC analyses showed an area under the curve of 0.82 (95% CI 0.68 to 0.95) for BMSi, higher than that for BMD at any location, which ranged from 0.64 (95% CI 0.47 to 0.82) for femoral neck (FN) BMD to 0.71 (95% CI 0.55 to 0.87) for LS-BMD. CONCLUSIONS: Patients who fracture while receiving BPs treatment have worse BMSi scores than BP-treated patients without fractures. The potential for BMSi to provide an additional osteoporosis treatment target should be explored.